ANALISIS KUALITAS AIR SUNGAI KALI SURABAYA BERDASARKAN PARAMETER FISIKA, KIMIA, DAN LOGAM BERAT PB DAN CD - Nadifa Nadifa Fairuz Cantika Zafarina; Syadzadhiya Qothrunada Zakiyayasin Nisa (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2026)
The Kali Surabaya River is one of the key sources of raw water in East Java, used for drinking water, industrial purposes, and irrigation. Various anthropogenic activities along the river basin have the potential to degrade water quality by increasing the levels of suspended solids and heavy metals. This study aims to analyze the water quality of the Kali Surabaya River based on physical, chemical, and heavy metal parameters at five observation points representing different land-use characteristics. Samples were collected using the purposive sampling method and then analyzed for pH, temperature, dissolved oxygen (DO), total suspended solids (TSS), lead (Pb), and cadmium (Cd). The test results were compared with Class I water quality standards as stipulated in Government Regulation No. 22 of 2021. The results showed that pH values ranged from 7.65 to 8.15, and all monitoring sites met the quality standards. Temperature ranged from 28.75 to 32.25°C, while DO ranged from 5.2 to 7.05 mg/L, with one sampling point failing to meet the quality standards. TSS concentrations ranged from 22 to 552 mg/L, with only one sampling point meeting the quality standards. Pb concentrations ranged from 0.0727 to 0.1695 mg/L, and all sampling points exceeded the quality standards, while Cd concentrations ranged from 0.00953 to 0.0152 mg/L, with 3 sampling points exceeding the quality standards. Variations in water quality are influenced by land-use characteristics, particularly industrial, agricultural, and residential activities. Overall, the TSS, Pb, and Cd parameters serve as indicators were identified as the primary parameters contributing to the deterioration of water quality in the Kali Surabaya River, indicating the need for sustainable pollution control measures. Keywords: Water quality; Kali Surabaya River; Total Suspended Solids (TSS); Lead (Pb); Cadmium (Cd).